Description of a new species of the genus Archaeoglenes Broun, 1893 (Coleoptera, Tenebrionidae, Phrenapatinae) from the Ryukyus, Japan, with ecological insights - Yanagi, Takeharu; Akita, Katsumi (Zootaxa, 2024)
A new species, Archaeoglenes fujikawai sp. nov. (Coleoptera, Tenebrionidae, Phrenapatinae), is described and illustrated from Okinawa-jima and Amami-ôshima Islands in the Ryukyu Archipelago. The present paper consistutes the first contribution to the Japanese members of the genus Archaeoglenes Broun, 1893 in about 40 years. Field surveys indicate that species within this genus have a strong ecological association with brown rot fungi.